Results of a multicentre dosimetry audit using a respiratory phantom within the EORTC LungTech trial. (September 2019) - Lambrecht, Marie Lara; Eaton, David J.; Sonke, Jan-Jakob; Nestle, Ursula; Peulen, Heike; Weber, Damien C.; Verheij, Marcel; Hurkmans, Coen W.
Highlights: Multi-institutional end-to-end test results for lung SBRT are presented. Beam output audit results do not correlate with phantom results and could be discarded in trial RTQA. Phantom point dose measurements are insufficient to ensure adequate plan delivery. Standardised QA acceptance criteria of lung SBRT are needed within and outside multicentre trials. Abstract: Introduction: The EORTC 22113-08113 LungTech trial assesses the safety and efficacy of SBRT for centrally located NSCLC. To insure protocol compliance an extensive RTQA procedure was implemented. Methods: Twelve centres were audited using a CIRS008A phantom. The phantom was scanned using target inserts of 7.5 mm and 12.5 mm radius in static condition. For the 7.5 mm insert a 4DCT was acquired while moving according to a cos 6 function. Treatment plans were measured using film and an ionization chamber. Wilcoxon's signed-rank tests were performed to compare the three plans across institutions. A Spearman correlation was calculated to evaluate the influence of factors such as PTV, slice thickness and total number of monitor units on the dosimetric results. Results: The reference output dose median [min, max] variation was 0.5% [−1.1, +1.5]. The median deviations between chamber doses and point-planned doses were 1.8% [−0.1; 6.7] for the 7.5 mm and 1.1% [−2.8; 5.0] for the 12.5 mm sphere in static situation and 3.2% [−3.2; 15.7] for the dynamic situation. Film gamma median pass rates were 92.0% [68.0, 99.0] for 7.5 mm static, 96.2% [73.0, 99.0] for 12.5 mm static and 71.0% [40.0, 99.0] for 7.5 mm dynamic. Wilcoxon's signed-rank tests showed that the dynamic irradiations resulted in significantly lower gamma pass rates compared to the 12.5 mm static plan ( p = 0.001). The total number of MUs per plan was correlated to both film and IC results. Conclusion: An end-to-end audit was successfully performed, revealing important variations between institutions especially in dynamic irradiations. This shows the importance of dosimetry audits and the potentials for further technique and methodology improvements.